Pengaruh Pertumbuhan Laba, Investment Opportunity Set dan Good Corporate Governance Terhadap Kualitas Laba Pada Perusahaan Sub Farmasi Yang Terdaftar di Bursa Efek Indonesia - Andika Hasburrahman (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research aims to examine the influence of profit growth, investment opportunity set and good corporate governance on earnings quality. This research uses multiple linear regression as a data analysis technique assisted by SPSS with the sample criteria being sub-pharmaceutical financial reports listed on the Indonesian stock exchange in 2018-2023. Based on these criteria, a sample of 10 companies was obtained over a 6 year financial reporting period. The research results show that profit growth (X1) does not have a significant effect on profit quality. Investment Opportunity Set (X2) has a positive and significant effect on earnings quality. Good Corporate Governance (X3) has no effect on quality